Image analysis of immediate full-arch prosthetic rehabilitations guided by a digital workflow: assessment of the discrepancy between planning and execution - Chmielewski, Krzysztof (Int J Implant Dent, 2019)
BACKGROUND: A dentition with adequate function and esthetics is essential for the well-being and quality of life. A full implant-retained fixed prosthetics is an ideal solution for fully edentulous arch, however requires complex planning, surgical, and prosthetic procedure. With the help of digital workflow, it becomes a predictable and fast solution for the dentists and the patients. This retrospective study analyzed the most advanced surgical approach in full-arch rehabilitation with dental implants and immediate loading using digital workflow. METHODS: Patient records of fully edentulous jaws treated in four clinical centers in Warsaw, Poland, were evaluated. Computer-assisted planning and surgical template fabrication were done using the planning software coDiagnostiX™, based on a pre-op cone beam computed tomography (CBCT) and scanned data of a plaster model. A post-op CBCT was acquired after the placement of four to six implants by the guided system. The influence of different surgical variables on the discrepancy between planning and execution was analyzed, together with the biomechanical indices. RESULTS: A total of nine patient records were selected of 12 edentulous jaws treated with 62 implants. The overall mean three-dimensional (3D) offset at the implant base was 1.60 mm, at the tip 1.86 mm. The mean angle of deviation was 4.89°, the mean implant stability quotient (ISQ) 70.42, and the insertion torque 35.58 Ncm. The 3D offsets were influenced by the gender of the patient, treated jaw, the diameter, and length of the implant. The angle of deviation was affected only by the treated jaw. Insertion torque was influenced by the treated jaw, the age of the patient, the length of the implant, tooth type, and the side of the jaw. DISCUSSION: Bone quality of the patient and implant preparation procedure influenced the discrepancy between the planning and the execution of the digitally guided implant placement. Dense bone—mandible, posterior area, young age, and man—and multiple preparations of the implant bed—wider and longer implant—could be suggested as risk factors. CONCLUSION: Digital workflow successfully enabled the immediate full-arch rehabilitation with a predictable outcome by different surgeons in multiple centers.